2020
DOI: 10.1007/s00436-020-06744-x
|View full text |Cite
|
Sign up to set email alerts
|

Besnoitia besnoiti–driven endothelial host cell cycle alteration

Abstract: Besnoitia besnoiti is an important obligate intracellular parasite of cattle which primarily infects host endothelial cells of blood vessels during the acute phase of infection. Similar to the closely related parasite Toxoplasma gondii, B. besnoiti has fast proliferating properties leading to rapid host cell lysis within 24-30 h p.i. in vitro. Some apicomplexan parasites were demonstrated to modulate the host cellular cell cycle to successfully perform their intracellular development. As such, we recently demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
0
9
0
6
Order By: Relevance
“…Toxoplasma gondii controls host cell cyclin E expression by the use of a MYR1-dependent effector protein, HCE1 (host cyclin E) which allows parasites to modulate E2F transcription factor target genes (Panas et al ., 2019 ). Another apicomplexan parasite, B. besnoiti was observed to upregulate the host cell cyclin E1 expression arresting cells in the G 1 phase (Velásquez et al ., 2020 ). Cyclin E1 is maximally active at the G 1 -to-S phase to induce DNA replication and is degraded during S/G 2 M (Caldon et al ., 2013 ), suggesting that E. bovis- infected cells are not able to exit from the G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxoplasma gondii controls host cell cyclin E expression by the use of a MYR1-dependent effector protein, HCE1 (host cyclin E) which allows parasites to modulate E2F transcription factor target genes (Panas et al ., 2019 ). Another apicomplexan parasite, B. besnoiti was observed to upregulate the host cell cyclin E1 expression arresting cells in the G 1 phase (Velásquez et al ., 2020 ). Cyclin E1 is maximally active at the G 1 -to-S phase to induce DNA replication and is degraded during S/G 2 M (Caldon et al ., 2013 ), suggesting that E. bovis- infected cells are not able to exit from the G 1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to T. gondii , a selective up-regulation of cyclin E1 was found in Besnoitia besnoiti -infected BUVECs thereby indicating parasite-driven host cell stasis in the G 1 phase or at G 1 -to-S phase transition. In line, the abundance of p27-kip1, a cyclin-dependent kinase (CDK) inhibitor being regulated at the G 1 /S boundary and involved in cyclin E1–CDK2 complex activity, was also found to be up-regulated in B. besnoiti -infected BUVECs (Velásquez et al ., 2020 ). So far, very little data exist on Eimeria -driven host cell cycle perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…T. gondii (strain RH) and N. caninum (strain NC-1) were maintained in vitro in permanent African green monkey kidney epithelial cells (MARC145) in DMEM (Sigma-Aldrich) as described elsewhere [ 12 ]. B. besnoiti (strain Bb Evora04) was propagated in Madin-Darby bovine kidney cells (MDBK) [ 11 , 59 ] in RPMI medium (Sigma-Aldrich). All cell culture media were supplemented with 500 U/mL penicillin, 50 μg/mL streptomycin (Sigma-Aldrich) and 5% FCS (Gibco TM ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the relevance of the tachyzoite replication in the acute phase of infection, several reports demonstrated that primary bovine umbilical vein endothelial cells (BUVEC) represent suitable host cells for in vitro replication of all three species [ 8 , 9 , 10 , 11 , 12 ], allowing fast tachyzoite replication in a setting close to the in vivo situation. During this replication process, one of the most demanded molecules is cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the host cells survive and support this development by an intense cytoskeletal re-organization (Hermosilla et al, 2008). Full macromeront formation takes up to 25 days and thereby considerably exceeds the merogonies of other closely related apicomplexans, such as T. gondii, Neospora caninum, or B. besnoiti (Conejeros et al, 2019;Velaśquez et al, 2019;Velaśquez et al, 2020a;Velaśquez et al, 2020b;Larrazabal et al, 2021). Besides cytoskeleton, E. bovis modulates several pathways and cellular functions, such as apoptosis, cholesterol biosynthesis, immune responses, or cell cycle progression to complete its intracellular development (Lang et al, 2009;Hamid et al, 2015;Velaśquez et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%